Macrophages, as a Promising Strategy to Targeted Treatment for Colorectal Cancer Metastasis in Tumor Immune Microenvironment - Zhang, Yingru; Zhao, Yiyang; Li, Qi; Wang, Yan (Frontiers in Immunology, 2021)
The tumor immune microenvironment plays a vital role in the metastasis of colorectal cancer. As one of the most important immune cells, Macrophages act as phagocytes, patrol the surroundings of tissues and remove invading pathogens and cell debris to maintain tissue homeostasis. Significantly, macrophages have a characteristics of highly plasticity and can be classified into different subtypes according to the different functions, which can undergo reciprocal phenotypic switching induced by different types of molecules and signaling pathways. Macrophages regulate the development and metastatic potential of colorectal cancer by changing the tumor immune microenvironment. In tumor tissues, the tumor-associated macrophages usually play a tumor-promoting role in the tumor immune microenvironment, and they are also associated with poor prognosis. This paper reviews the mechanisms and stimulating factors of macrophages in the process of colorectal cancer metastasis, intends to indicate that targeting macrophages may be a promising strategy in colorectal cancer treatment.